Stem Cell Therapy and Innate Lymphoid Cells - Divya Verma; Mukesh Verma; Rangnath Mishra (Hindawi Limited, 2022)
Innate lymphoid cells have the capability to communicate with other immune cell types to coordinate the immune system functioning during homeostasis and inflammation. However, these cells behave differently at the functional level, unlike T cells, these cells do not need antigen receptors for activation because they are activated by the interaction of their receptor ligation. In hematopoietic stem cell transplantation (HSCT), T cells and NK cells have been extensively studied but very few studies are available on ILCs. In this review, an attempt has been made to provide current information related to NK and ILCs cell-based stem cell therapies and role of the stem cells in the regulation of ILCs as well. Also, the latest information on the differentiation of NK cells and ILCs from CD34+ hematopoietic stem cells is covered in the article.